Digital Transformation Initiatives in Gauteng Provincial Government - Makhubele, Nomsa Tintswalo (University of the Witwatersrand, Johannesburg, 2023)
Digital transformation is a crucial aspect of modernising the public sector in South Africa. The Gauteng Provincial Government (GPG) has been leading the implementation of various digital technologies to improve efficiency and citizen engagement. One of the digital transformation initiatives implemented in Gauteng is e-recruitment, which aims to streamline the hiring process. This qualitative study used a purposive sampling of HR personnel to investigate the acceptance of e-recruitment in the Gauteng Provincial Government, which has fourteen provincial departments. The study was conducted using focus group interviews to understand the general experience that the HR officials have with the e-recruitment system, its impact and effectiveness, and how these relate to digital transformation. A study sample of ten (10) HR personnel participated in the study. The study's findings indicated that while e-recruitment is perceived as user- friendly and advantageous, its benefits were outweighed by several drawbacks. Inadequate IT infrastructure, a deficiency in customer engagement tools, and a lack of core process and workforce enablement were identified as factors that diminished the perceived benefits of the system. These drawbacks can influence an organisation's digital transformation journey. It is recommended that Gauteng address its Digital Application and Impact dimensional elements urgently. Addressing these issues is crucial to ensuring that Gauteng maximizes the return on its investment and fast-tracks its digital transformation. The study confirmed that in the enterprise context, such as public service, where adoption is mandatory, a lack of perceived benefits does not necessarily lead to system abandonment, but it can affect its digital transformation. System adoption can be sustained if one of the two factors of TAM is in place, as was the case with the ease of use sustaining the use of the system alongside the departmental strategy of digital transformation and modernisation
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Public Sector; Digital Transformation; Digital Maturity; Digitalisation; Gauteng Provincial Government and e-recruitment; UCTD; SDG-8: Decent work and economic growth